PHYSIOLOGY AND YIELD OF THREE SOYBEAN (GLYCINE MAX (L.) MERRILL) CULTIVARS DIFFERENT IN MATURITY TIMING AS AFFECTED BY WATER DEFICIENCY - Basal, Oqba; Szabó, András (LIFE: International Journal of Health and Life-Sciences, 2018)
Water deficiency is globally increasing as a direct result of climatic changes, threatening food production stability, especially of drought-susceptible crops, to which soybean (Glycine max (L.) Merrill) belongs. Soybean is mainly important because of its high protein and oil content.A field experiment was conducted in Debrecen, Hungary in 2017. Three soybean cultivars, different in maturity timing (very early-, early-, and middle-timing cultivars), were grown under two irrigation regimes; non-irrigated (NI) and fully-irrigated (FI) regime, in order to study the effect of water deficiency on the physiology and the yield of the above-mentioned cultivars.The yield of the three cultivars was increased when irrigation was applied, and though the increase was insignificant, yet the physiological traits were noticeably, and significantly in certain traits, different between the two irrigation regimes.It was concluded that water deficiency affects the physiology and the yield of soybean, and that the effect output is cultivar-dependent. More traits at different growth stages are needed to best understand water deficiency influence on soybean.